Laborer’s Efficiency of Gypsum Plastering in Sulaimani City’s Projects - Abdullah, Atta Shekh Karim; Ali, Noori Sadeq; Abdullah, Payjor Ali Shonm (Kurdistan Journal of Applied Research, 2019)
In this study, the Laborer’s Efficiency (LE) in building projects in Sulaimani City practically on field sites were investigated for Gypsum plastering (GP). Accordingly, four constructional different buildings as Multistory, commercial and houses were considered. Overall 11 main important factors during 30 practical records on field sites were practically observed. As a result, for the first time the Laborers’ Efficiency (LE) was measured and classified into three categories high, medium and low for two specific heights which were 0-2 m and 2-3 meters height of walls. On the other hand, it concluded that the LE for the height of 0-2m affected on LP from 15.18 to 21.35m2/hr., with a proportion of 40.6%. In addition to the LE affected-on LP for the height of 2-3m and varied the LP range between 13.33-15 m2/hr., with a proportion of 12.5%.